Antijamming Design and Analysis of a Novel Pulse Compression Radar Signal Based on Radar Identity and Chaotic Encryption - Jian Dai (IEEE Access, 2020)
As the use of radar and radar jammers increases, a radar device is likely to face interference from jammers or other radar devices. Traditional phase-coded pulse compression radar devices are widely used, but these tools struggle to overcome jamming and mutual interference. To solve this problem, we propose a novel chaotic-encrypted pulse compression radar signal based on radar identity (ID). Each radar has its own ID, which is encrypted with different chaotic binary sequences in every pulse period. The ambiguity function calculated for the coded radar signal is thumbtack-shaped, indicating that the signal has a good resolution. The received signal is used to range and decrypt in two channels: the range channel and the radar ID channel. The signals of the two channels are analyzed separately. Analyses of anti-barrage jamming and anti-mutual interference show that both channels perform well in terms of antijamming, while the antijamming ability is influenced by the processing gain, bit error rate (BER) and correlation function. In addition, the dual-channel antijamming method further improves the radar antijamming ability. The simulation result verifies the strong antijamming ability and high range resolution of the proposed radar signal, and the proposed antijamming method performs much better than the traditional phase-coded pulse compression radar signal in the antijamming scenario.